ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA KELAS VIII DI SMP N 2 LUHAK NAN DUO KABUPATEN PASAMAN BARAT (JURNAL LEMMA, 2022)
This research is a descriptive research with a qualitative approach. This study aims to find out how the errors made by students in working on math problems in class VIII4 students at SMP N 2 Luhak Nan Duo, West Pasaman Regency. The subjects in this study were VIII4 class students at SMP N 2 Luhak Nan Duo, West Pasaman Regency. The taking of research subjects was based on the results of essay tests on mathematics learning given to all students of class VIII4, totaling 26 students. The data analysis technique uses data reduction, data presentation, conclusion drawing, and data validity (triangulation). The results of this study indicate that students perform Zeroing error indicators, namely (1) Careless Errors (CaE) or factual errors, students do not consider the components in the question to be known and asked the question because students are not used to doing it every time they solve problems and students are lazy to write components because According to students it takes a long time to solve the problem. (2) Concept Errors (CoE) or conceptual errors, students do not master the concepts in problem solving because students do not understand examples and calculations. (3) Application Errors (ApE) or principle errors, students do not know the formula or know the formula so that students cannot solve the problem because students are in a hurry so they forget the formula to solve the problem. And (4) Test Talking Errors (TTE) or student operating errors did not complete the answers and final conclusions because there was no concentration disturbed by the answers of friends.